2004
DOI: 10.1074/jbc.m313155200
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Estrogen Receptor α with 3-Methyladenine DNA Glycosylase Modulates Transcription and DNA Repair

Abstract: Estrogen receptor ␣ (ER␣) interacts with basal transcription factors, coregulatory proteins, and chromatin modifiers to initiate transcription of the target genes. We have identified a novel interaction between ER␣ and the DNA repair protein 3-methyladenine DNA glycosylase (MPG) thereby providing a functional link between gene expression and DNA repair. Interestingly, the ER␣-MPG interaction was enhanced by the presence of estrogen response element (ERE)-containing DNA. In vitro pull-down assays indicated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 50 publications
0
42
0
Order By: Relevance
“…A primary mechanism involves interactions with proteins that regulate transcription. It has been reported that methyl purine DNA glycosylase associates with the transcriptional repressor MBD1 to cooperatively inhibit gene expression (34), and 3-methyladenine DNA glycosylase interacts with estrogen receptor ␣ to modulate estrogen-mediated transcription (35). There is also evidence that TDG modulates transcription through interactions with hormone receptors (36, 37), transcription factors (38), and coactivators such as the CPB͞p300 acetylase complex (39).…”
Section: Discussionmentioning
confidence: 99%
“…A primary mechanism involves interactions with proteins that regulate transcription. It has been reported that methyl purine DNA glycosylase associates with the transcriptional repressor MBD1 to cooperatively inhibit gene expression (34), and 3-methyladenine DNA glycosylase interacts with estrogen receptor ␣ to modulate estrogen-mediated transcription (35). There is also evidence that TDG modulates transcription through interactions with hormone receptors (36, 37), transcription factors (38), and coactivators such as the CPB͞p300 acetylase complex (39).…”
Section: Discussionmentioning
confidence: 99%
“…Thymine DNA glycosylase has been reported to both activate and repress gene transcription by a variety of mechanisms, including binding to hormone receptors (29,30), interacting with transcription factors (31), and associating with CBP͞p300 acetylase, which remodels chromatin and activates transcription through histone acetyltransferase activity (32). Methylpurine DNA glycosylase has a synergistic effect on gene silencing by interacting with the methyl CpG-binding domain protein 1 (MBD1) transcriptional repressor (33) and 3-methyladenine DNA glycosylase interacts with estrogen receptor ␣ to inhibit gene transcription (34). Thus, DNA glycosylases are linked to the process of gene regulation by physical interactions that modulate the activities of transcription factors, receptors, and chromatin-remodeling proteins.…”
Section: Multiple Mechanisms For Regulation Of Gene Transcription By Dnamentioning
confidence: 99%
“…www.aacrjournals.org estrogen-responsive gene expression have been observed with other ERa-associated DNA repair proteins (14,22,29). It has been suggested that these proteins may help to stabilize the transcription complex so that DNA repair and transcription can occur simultaneously.…”
Section: Nm23-h1 Interaction With Eramentioning
confidence: 89%
“…Interestingly, we have identified other DNA repair proteins, 3-methyladenine DNA glycosylase (MPG) and flap endonuclease (FEN-1), which associate with ERa and influence estrogenresponsive gene expression (22,29). Like NM23-H1, MPG and FEN-1 increase ERa-ERE binding in gel mobility shift assays and decrease transcription of a reporter plasmid in transient transfection assays.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation